Alpha-lactalbumin: A new carrier for vitamin D3 food enrichment. (March 2015) - Delavari, Behdad; Saboury, Ali Akbar; Atri, Maliheh Sadat; Ghasemi, Atiyeh; Bigdeli, Bahareh; Khammari, Anahita; Maghami, Parvaneh; Moosavi-Movahedi, Ali A.; Haertlé, Thomas; Goliaei, Bahram
Abstract: Vitamin D is a fat-soluble regulatory vitamin maintaining blood calcium and phosphorus concentrations within a narrow physiological range. Binding to an appropriate delivery system can enhance vitamin D3 solubility, simplify its transport, protect it from degradation and increase its bioavailability. Alpha-lactalbumin as a milk protein is a good candidate for a vitamin encapsulation. Binding properties and conformational change of bovine apo alpha-lactalbumin upon interaction with vitamin D3 were investigated by calorimetry, spectroscopy and by molecular docking. Tryptophan fluorescence quenching indicates that the protein conformation changes in the presence of vitamin D3 . However, according to far UV CD results, the secondary structure of the protein was altered in the presence of vitamin D3 . The molecular modeling showed that Van der Waals interactions, hydrogen bond and hydrophobic interactions play a major role in the binding of vitamin D3 to the alpha-lactalbumin hydrophobic pocket. The particle size of alpha-lactalbumin and vitamin D3 complex is much larger than the native protein. Surprisingly, in the presence of vitamin D3, the thermal stability of the protein decreases. The binding constant and standard Gibbs free energy change (Δ G °) of binding vitamin D3 to the protein obtained from ITC are 3.66 × 10 5  M −1 and −7.6 kcal mol −1, respectively, what agrees with results obtained by measurement of fluorescence and by molecular docking. The formed complex is a suitable candidate in order to enrich the low-fat food and non-alcohol drinks. According to the results, alpha-lactalbumin can be introduced suitable carrier for vitamin D3 . Graphical abstract: Highlights: α-La can be introducedsuitable carrier for encapsulation of vitamin D3 . α-La contains one binding site for vitamin D3. The particle size of complex formed between α-La and vitamin is much larger than the native protein. The conformation of protein changes and hydrophobic surface of the α-La increases. Complex formation decreases the heat stability of the protein.